The Influence of Current Ratio, Debt to Equity Ratio, And Total Asset Turnover Ratio on Profitability of Transportation Companies Listed On the Indonesia Stock Exchange 2014-2018 - Talisa Qamara; Ani Wulandari; Agus Sukoco; Joko Suyono (IJESEMS : International Journal of Engineering Science Educatioon and Management System, 2020)
This study aims to analyze whether there are simultaneous effects of Current Ratio, Debt to Equity Ratio, and Total Asset Turnover to Pofitability (Return On Asset) on Transportation Company Listed at Indonesia Stock Exchanged. This research use quantitative method. The population on this research is transportation companies listed at Indonesia Stock Exchange (IDX) and continuously published financial reports in 2014-2018. Based on the purposive sampling method, from 71 transportation companies globally converged into 10 transportation companies, so that the data obtained were 50 observation. The analytical method used is multiple linear regression analysis. The results of the study are Current Ratio and Debt to Equity Ratio does not partially affect ROA, while Total Asset Turnover has a partial effect on ROA. And the three independent variables (CR, DER and TATO) simultaneously influence the dependent variable, namely profitability (ROA)